Foucault for architects - Fontana-Giusti, Gordana. (Thinkers for architects., 2013)
"Offering an excellent entry point into the remarkable work of Michel Foucault, this book provides a focused overture suitable for architects, designers, urban designers, students of architectural design and related histories and theories. Michel Foucault has had a significant impact on various aspects of architecture and its critical discourse. This book focuses on a number of subject areas, historical and theoretical issues addressed by Foucault that have been relevant for architectural knowledge, its history and its practice. "--